THE CORRELATION BETWEEN EXPLICIT GRAMMATICAL KNOWLEDGE AND WRITING ABILITY OF EFL STUDENTS - Hayyi, Alfi (2014)
This research was carried out correspondingly with the background of the importance of grammatical knowledge in enhancing writing ability. This is demonstrated by some findings emerged amongst researchers who inquisitively explored whether the explicit grammatical knowledge accounts for writing ability or not. In this notion, various findings regarding the above-mentioned problem involving slight, moderate, strong, very strong correlation, and no-correlation between the two variables, had been ultimately found. Hence, this study was aimed at investigating the correlation between explicit grammatical knowledge and writing ability of EFL students. This research is a quantitative research with explanatory correlation design. The subjects of the research were the 36 twelfth grade students in a Senior High School in Bandung. The degree of correlation between the two variables observed was then obtained by giving achievement test to the participants using two instruments namely explicit grammatical judgment test and writing ability test. Based on the result of the research, the correlation degree between the two variables was at the point of 0.867 and accordingly it can be concluded that the correlation between explicit grammatical knowledge and writing ability of EFL student was very strong. From the findings, it is recommended that the teacher should take into account the fact that the two variables are correlated. Consequently a teaching methodology, by which the grammar knowledge can be reinforced, can be applied as follow-up action of this present study result for the sake of students' writing ability development. Keywords: Explicit Grammatical Knowledge, Writing Ability, EFL Students Penelitian ini dilatarbelakangi oleh pentingnya pengetahuan mengenai tata bahasa untuk meningkatkan kemampuan menulis. Hal ini terlihat dari beberapa penemuan dari banyak peneliti yang secara telaten mencari tahu apakah pengetahuan tentang tata bahasa memiliki pengaruh terhadap kemampuan menulis tersebut. Dalam hal ini, bermacam kesimpulan mengenai hal ini meliputi adanya hubungan yang sedang, kuat, sangat kuat dan bahkan tidak adanya hubungan diantara kedua variable akhirnya ditemukan. Oleh karena hal tersebut, penelitian kali ini dimaksudkan untuk menginvestigasi hubungan antara pengetahuan yang eksplisit mengenai tata bahasa dengan kemampuan menulis tersebut. Penelitian ini adalah salah satu bentuk dari penelitian kuantitatif dengan desain explanatory (bersifat menjelaskan). Subjek penelitian ini meliputi 36 siswa kelas 12 dari sebuah sekolah menengah atas di Bandung. Tingkat korelasi antara kedua variable tersebut kemudian ditentukan dengan memberikan 2 macam tes kemampuan kepada subjek tersebut yang meliputi tes kemampuan tata bahasa dan kemampuan menulis. Berdasarkan hasil dari penelitian ini, derjat hubungan antara kedua variable tersebut mencapai angka 0, 867 dan angka ini mengimplikasikan bahwa korelasi antara pengetahuan tata bahasa dengan kemampuan menulis sangatlah kuat. Hasil ini merekomendasikan kepada para pengajar untuk mempertimbangkan fakta ini. Oleh karena itu, pengajaran untuk meningkatkan kemampuan tata bahasa siswa bisa dilakukan sebagai bentuk pertimbangannya demi meningkatkan perkembanga kemampuan menulis mereka. Kata Kunci: korelasi, pengetahuan tata bahasa, kemampuan menulis, pelajar EFL